2008
DOI: 10.1017/s0022149x08046920
|View full text |Cite
|
Sign up to set email alerts
|

Helminth communities of the autochthonous mustelids Mustela lutreola and M. putorius and the introduced Mustela vison in south-western France

Abstract: This study presents the first comprehensive helminthological data on three sympatric riparian mustelids (the European mink Mustela lutreola, the polecat M. putorius and the American mink M. vison) in south-western France. One hundred and twenty-four specimens (45 M. lutreola, 37 M. putorius and 42 M. vison) from eight French departments were analysed. Globally, 15 helminth species were detected: Troglotrema acutum, Pseudamphistomum truncatum, Euryhelmis squamula, Euparyphium melis and Ascocotyle sp. (Trematoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 25 publications
(50 reference statements)
5
26
1
1
Order By: Relevance
“…F. martis is a gastropod-transmitted nematode commonly observed in mustelids (Kontrimavichus and Delyamure 1985) with documented findings throughout Europe except for the Balkan Peninsula (e.g. Sołtys 1962;Prokopič 1965;Mituch 1972;Schellner 1982;Zimmerli 1982;Miquel et al 1992;Torres et al 1996Torres et al , 1996Torres et al /1997Torres et al , 2003Torres et al , 2008Siderovich and Anisimova 1997;Shimalov andShimalov 2001, 2002;Anisimova 2002;Segovia et al 2007). Other Filaroides species, in particular Filaroides (Oslerus) osleri, are considered pulmonary nematodes parasitizing dogs (Eckert 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…F. martis is a gastropod-transmitted nematode commonly observed in mustelids (Kontrimavichus and Delyamure 1985) with documented findings throughout Europe except for the Balkan Peninsula (e.g. Sołtys 1962;Prokopič 1965;Mituch 1972;Schellner 1982;Zimmerli 1982;Miquel et al 1992;Torres et al 1996Torres et al , 1996Torres et al /1997Torres et al , 2003Torres et al , 2008Siderovich and Anisimova 1997;Shimalov andShimalov 2001, 2002;Anisimova 2002;Segovia et al 2007). Other Filaroides species, in particular Filaroides (Oslerus) osleri, are considered pulmonary nematodes parasitizing dogs (Eckert 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, fitness-associated traits of parasites are higher in the native host (Dunn and Dick 1998;Roche et al 2010;Gendron et al 2012;Lacerda et al 2012;Ondračková et al 2012). The prevalence and abundance (or intensity) of native helminths has been compared between introduced and native definitive hosts (Kelly et al 2009), including the American mink in Europe (Shimalov and Shimaliv 2001;Torres et al 2003Torres et al , 2008. Each of these studies indicated a paucity of helminth fauna diversity (and prevalence) in the introduced mink relative to native hosts (Torres et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and abundance (or intensity) of native helminths has been compared between introduced and native definitive hosts (Kelly et al 2009), including the American mink in Europe (Shimalov and Shimaliv 2001;Torres et al 2003Torres et al , 2008. Each of these studies indicated a paucity of helminth fauna diversity (and prevalence) in the introduced mink relative to native hosts (Torres et al 2008). Prior to the current study, differences in macroparasite fecundity within introduced and native definitive hosts do not appear to have been explored, yet this is a fundamental aspect of parasite transmission potential.…”
Section: Discussionmentioning
confidence: 99%
“…truncatum has been recorded in a broad range of carnivore species; otter (Schuster et al 1988), polecat (Mustela putorius Linnaeus, 1758) (Shimalov and Shimalov 2002), European mink (Mustela lutreola Linnaeus, 1761) (Anisimova 2004;Torres et al 2008), stoat (Mustela erminea Linnaeus, 1758), weasel (Mustela nivalis Linnaeus, 1766) (Shimalov and Shimalov 2001b), wolverine (Gulo gulo Linnaeus, 1758) (Healy 1970), red fox (Vulpes vulpes Linnaeus, 1758) (Schuster et al 1999(Schuster et al , 2001bSaeed et al 2006), wolf (Canis lupus Linnaeus, 1758) (Shimalov and Shimalov 2000), grey seals (Halichoerus grypus Fabricius, 1791) (Bergman 2007) and Caspian seals (Phoca caspica Gmelin, 1788) (Kuiken et al 2006). P. truncatum has also been found to infect domestic animals; cats (Traldi and Manca 1982), where it was described as Distomum conus (Creplin 1825) and dogs (Healy 1970).…”
Section: Introductionmentioning
confidence: 98%